Does membership in international organizations increase governments’ credibility?: testing the effects of delegating powers - Dreher, Axel; Voigt, Stefan (Journal of comparative economics, 2011)
This paper analyzes whether nation-state governments can increase their credibility by becoming members of international organizations. It is hypothesized that the degree of delegation to international organizations can improve the credibility of nation-state governments. This hypothesis is tested by introducing three new indicators for international delegation. On the basis of panel data for up to 136 countries and the time period from 1984 to 2004, membership in international organizations is significantly and robustly linked with better credibility, here proxied for by country risk ratings.